PEDAGOGICAL FOUNDATIONS IN THE PROFESSIONAL TRAINING OF FUTURE TEACHERS OF DRAWING SCIENCE - Faxriddinov Muhammad Faxriddin o‘g‘li, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
The field of drawing science, while often perceived as an artistic endeavor, encompasses a rich tapestry of pedagogical principles that are essential for the professional training of future educators. The interplay between artistic skills and pedagogical knowledge is critical in nurturing effective drawing teachers who can inspire and educate their students. This essay explores the key pedagogical foundations necessary for the professional training of future drawing science teachers, focusing on curriculum development, instructional strategies, assessment practices, and the integration of technology.